Evidence of neuromuscular fatigue after prolonged cycling exercise - Lepers, R.; Hausswirth, C.; Maffiuletti, N.; Brisswalter, J.; van Hoecke, J. (Medicine & Science in Sports & Exercise, 2000)
PURPOSE: The purpose of this study was to analyze the effects of prolonged cycling exercise on metabolic, neuromuscular, and biomechanical parameters. METHODS: Eight well-trained male cyclists or triathletes performed a 2-h cycling exercise at a power output corresponding to 65% of their maximal aerobic power. Maximal concentric (CON; 60, 120, 240 degrees x s(-1)), isometric (ISO; 0 degrees s(-1)), and eccentric (ECC; -120, -60 degrees x s(-1)) contractions, electromyographic (EMG) activity of vastus lateralis (VL) and vastus medialis (VM) muscles were recorded before and after the exercise. Neural (M-wave) and contractile (isometric muscular twitch) parameters of quadriceps muscle were also analyzed using electrical stimulation techniques. RESULTS: Oxygen uptake (VO2), minute ventilation (VE), and heart rate (HR) significantly increased (P < 0.01) during the 2-h by, respectively, 9.6%, 17.7%, and 12.7%, whereas pedaling rate significantly decreased (P < 0.01) by 21% (from 87 to 69 rpm). Reductions in muscular peak torque were quite similar during CON, ISO, and ECC contractions, ranging from 11 to 15%. M-wave duration significantly increased (P < 0.05) postexercise in both VL and VM, whereas maximal amplitude and total area decreased (VM: P < 0.05, VL: NS). Significant decreases in maximal twitch tension (P < 0.01), total area of mechanical response (P < 0.01), and maximal rate of twitch tension development (P < 0.05) were found postexercise. CONCLUSIONS: A reduction in leg muscular capacity after prolonged cycling exercise resulted from both reduced neural input to the muscles and a failure of peripheral contractile mechanisms. Several hypothesis are proposed to explain a decrease in pedaling rate during the 2-h cycling with a constancy of power output and an increase in energy cost.